Online Machine Engineering (OME) - Tan, Kok Hui. (2008)
This dissertation discusses on the hardware and software requirements, the system architecture and connection to the equipment and shop floor network as well as the database types and functions. The later part of the dissertation also deals on the Graphical User Interfaces and their various functions.